Combustion process of homogeneous charge compression ignition engine using numerical modeling - Md Zain @ Abdul Rahman, Najihah (2014)
A zero dimensional thermodynamic numerical model is developed to simulate the combustion characteristics and performance of a four stroke gasoline engine using homogeneous compression combustion ignition (HCCI) method. This model which applies the first law of thermodynamics for a closed system is inclusive of empirical model for predicting the important parameters for engine cycles: the combustion timing and mass burnt fraction during the combustion process. The hypothesis is the increasing intake temperature can reduce the combustion duration and the fuel consumption at wide range of equivalence ratio, resulting in decreasing peak pressure and friction losses, and hence, increasing the engine efficiency. The intake temperature were increased from 373-433 K with increment of 20 K. The engine was operated over a range of equivalence ratios of 0.2 to 0.5 at constant engine speed of 1200 rpm and intake pressure of 89,950 K Pa. Simulations were performed using Simulink® under different engine operating conditions. The model was successfully developed to predict the combustion characteristics and performance. Validations show good agreements between the experimental data and simulation results. Increasing intake temperature allows reducing the combustion duration by 0.99 °CA and 0.26 °CA at equivalence ratios of 0.2 and 0.5, respectively, followed by decreasing the heat released to the wall about 22.79%. The brake power reduces up to 3.56% at any equivalence ratios. However, the brake specific fuel consumption decreases about 6.09%-5.76% at 0.2-0.5 of equivalence ratios, respectively. Increasing intake temperature does not increase the power output. However, it is able to improve the efficiency at richer mixture as the fuel consumption and brake specific fuel consumption also can be decreased.